Seed Grant Programs to Promote Community Transformation in Higher Education Institutions - Gabriella Coloyan Fleming; Sydni Alexa Cobb; Del Watson; Audrey Boklage; Maura Borrego; Lydia Contreras; Christine Julien (MDPI AG, 2024)
Used in higher education for many decades, seed grants are now beginning to be applied as a strategy to advance diversity, equity and inclusion goals, including rebuilding community post-pandemic. There is little research on the effectiveness of seed grants for such communal goals. This work is innovative in two key ways. First, these seed grants focus on promoting a strong sense of community at the institution rather than promoting individual investigators and research projects. Second, engaging students and staff as principal investigators (PIs) disrupts power structures in the academy. We present a systematic analysis of seed grant project reports (n = 45) and survey data (n = 56) from two seed grant programs implemented at the same institution. A diverse set of projects was proposed and funded. Projects had a positive impact on awardees and their departments and colleges. Seed grant program activities were successful at building community among awardees and recognizing individual efforts. Most noteworthy are the career development opportunities for graduate students, postdocs and staff, which are afforded by changes to PI eligibility. We conclude that seed grant programs have the potential for organizational learning and change around community building in higher education.